A KNOWLEDGE TRANSLATION INITIATIVE TO ENHANCE EVIDENCE-INFORMED CLINICAL MANAGEMENT OF ACHILLES TENDINOPATHY: THE PURPOSE, PROCESS AND OUTCOMES OF THE BC TENDINOPATHY TOOLKIT. Issue 9 (10th May 2013) - Hoens, A M; Ezzat, A; Anthony, J; Scott, A; Yates, M; Justesen, J R; Hughes, D
Abstract : Introduction: Translation of knowledge to practice in health care is a significant challenge.1 2 – 3 This presentation describes the purpose, process and preliminary outcomes of a knowledge translation (KT) initiative undertaken by a unique partnership of physical therapy researchers, educators and expert clinicians to address the gap between evidence and practice in the management of Achilles tendinopathy. Methods: Physiotherapy clinicians in British Columbia requested evidence-informed guidance on the management of tendinopathy. To address this need, the provincial Physical Therapy Knowledge Broker assembled a team of researchers, educators and expert clinicians with the mandate to develop, disseminate and implement a toolkit of decision aids to guide clinical decision-making for Achilles Tendinopathy. The process to develop the toolkit involved the following components: (1) identification of the purpose and scope of the project (2) agreement on the processes for selection of content and format (3) creation of a mechanism for resolution of conflicting opinion (4) an iterative feedback process with stakeholders and (4) the incorporation of concepts and strategies from the knowledge translation and implementation science literature to support the stages of knowledge synthesis, dissemination and implementation.1 2 3 – 4 Results: The 'Tendinopathy Toolkit' included: (1) a tabulated summary of the evidence for manual therapy, exercise, low level laser therapy, ultrasound, extracorporeal shock wave therapy, iontophoresis using dexamethasone, taping, orthotics, night splints and braces, heel raise inserts, needling techniques, and the appropriate outcome measures for this population (targeted 'take home messages' and clinical implications for each were also included); (2) an algorithm to guide the sequence of interventions; (3) and appendices including (a) exercise programmes (b) low level laser dosage calculation (c) tabulated details for each article reviewed and (d) a review of common medical interventions. The second phase of the initiative—utilization of strategies to enhance implementation and uptake of the toolkit—is currently being undertaken. Discussion: Clinicians want to provide evidence-informed management of tendinopathy but many struggle with accessing, appraising and synthesising the vast array of literature available on this topic. This KT initiative highlights the need for, challenges associated with, evidence-informed process for and positive response to the development of decision aids synthesising the current evidence to guide clinical management of this patient population.